Maskulinitas tokoh utama pria pada film Вокзал Для Двоих (Stasiun untuk Berdua) karya Eldar Ryazanov - Aviandy, Mochamad; Reisha Anindyapradha Rusli (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2024)
This study analyzes the representation of masculinity in the male main character depicted in Eldar Ryazanov's film Вокзал Для Двоих (Railway Station for Two), which was released in 1982. This study aims to describe and interpret the portrait of masculine characteristics shown in Platon Sergeyevich Ryabinin as the leading male character in this film. The method used in this research is a qualitative approach in the form of the descriptive analytical method. The theory used to examine representations in film scenes and dialogues is Stuart Hall's representation theory and supported by Roland Barthes' semiotic theory. This research shows that through both parts of the film Вокзал Для Двоих (Railway Station for Two) (1982), Platon Sergeyevich Ryabinin as the male lead character exhibits masculine characteristics based on seven characteristics expressed by Janet Saltzman Chafetz, namely physical appearance, functional, sexual, emotional, intellectual, interpersonal, and other personal characteristics of the character.